2009
DOI: 10.1002/chem.200802601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Stereogenic Amides and Ketones by Enantioselective Conjugate Addition of 1,4‐Dicarbonyl But‐2‐enes

Abstract: In the conjugate addition reaction of a alpha,beta-unsaturated compound, the new stereogenic center is created in the beta-position. In contrast, conjugate addition to 1,4-dicarbonyl but-2-enes will generate an alpha-stereogenic center with respect to one of the carbonyl groups, which informally, can be considered as an inversion of normal reactivity patterns or Umpolung. In this paper, we demonstrate that chiral bicyclic guanidine can catalyze the addition of 1,3-dicarbonyl compounds to 1,4-dicarbonyl but-2-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Chiral guanidines have been developed as an important type of organocatalyst in numerous asymmetric reactions, particularly the axially chiral guanidine and the C 2 ‐symmetric bicylic guanidines 16. In the past few years, we have developed a series of C 2 ‐symmetric bicyclic‐guanidine‐catalyzed reactions with excellent results, such as the Diels–Alder reaction,17a protonation,17bd the Mannich reaction,17e decarboxylative reaction,17f the Michael reaction,3j, 14d, e, 17gi vinylogous amination,17j and amination 17k. Notably, in 2007, we reported a highly enantioselective Michael addition of dithiomalonates to 2‐cyclopentenone catalyzed by bicyclic guanidine ( 1 ) [Scheme , Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Chiral guanidines have been developed as an important type of organocatalyst in numerous asymmetric reactions, particularly the axially chiral guanidine and the C 2 ‐symmetric bicylic guanidines 16. In the past few years, we have developed a series of C 2 ‐symmetric bicyclic‐guanidine‐catalyzed reactions with excellent results, such as the Diels–Alder reaction,17a protonation,17bd the Mannich reaction,17e decarboxylative reaction,17f the Michael reaction,3j, 14d, e, 17gi vinylogous amination,17j and amination 17k. Notably, in 2007, we reported a highly enantioselective Michael addition of dithiomalonates to 2‐cyclopentenone catalyzed by bicyclic guanidine ( 1 ) [Scheme , Eq.…”
Section: Methodsmentioning
confidence: 99%
“…While the Friedel-Crafts alkylations with a,b-unsaturated substrates through a conjugate addition result in the formation of a stereogenic center in the b-position to a carbonyl group, the reaction with 2-butene-1,4-diones generates an a-stereogenic center with respect to one of the carbonyl groups. According to Tan, [17] as this a-stereogenic center is obtained through the action of a nucleophile (the indole nucleus) on an unsaturated ketone, this can be considered as an inversion of the normal reactivity pattern or umpolung reactivity [18] (Scheme 1). To date, only two reports on asymmetric nucleophilic additions (Michael reactions) to 1,4-dicarbonyl-but-2-enes have been published; [17,19] one of them involving arylboronic acids and the other 1,3-dicarbonyl compounds as nucleophiles, while the Friedel-Crafts reaction of nucleophilic heterocycles with this kind of acceptors has not been described so far.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tan, [17] as this a-stereogenic center is obtained through the action of a nucleophile (the indole nucleus) on an unsaturated ketone, this can be considered as an inversion of the normal reactivity pattern or umpolung reactivity [18] (Scheme 1). To date, only two reports on asymmetric nucleophilic additions (Michael reactions) to 1,4-dicarbonyl-but-2-enes have been published; [17,19] one of them involving arylboronic acids and the other 1,3-dicarbonyl compounds as nucleophiles, while the Friedel-Crafts reaction of nucleophilic heterocycles with this kind of acceptors has not been described so far. (E)-1,4-Diaryl-2-butene-1,4-diones 2 are challenging substrates on account of their functionalization with two carbonyl groups conjugate to a common trans-double bond.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, unsaturated 1,4-dicarbonyl compounds, such as 1,4-ketoesters [68], 1,4-diketones [9], 1,4-ketoamides [910] and dialkylfumarates [11], have been the substrates for this reaction. The reaction products can undergo further chemical transformations, allowing the possibility of cascade reactions, making the method attractive for the synthesis of several valuable compounds, such as drugs and natural products.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction products can undergo further chemical transformations, allowing the possibility of cascade reactions, making the method attractive for the synthesis of several valuable compounds, such as drugs and natural products. Tan et al performed the addition of 1,3-alkylthiomalonates to 1,4-dicarbonylbut-2-enes, catalyzed by chiral bicyclic guanidines [7,9,12]. Xiao et al reported the addition of nitroalkanes to 4-oxo-enoates, using chiral urea derivatives [7].…”
Section: Introductionmentioning
confidence: 99%